1976
DOI: 10.1111/j.1471-0528.1976.tb00800.x
|View full text |Cite
|
Sign up to set email alerts
|

FIBRINOLYTIC ACTIVITY IN UTERO AND BLEEDING COMPLICATIONS WITH INTRAUTERINE CONTRACEPTIVE DEVICES

Abstract: Increased menstrual loss and irregular uterine bleeding are major drawbacks to acceptibility of intrauterine contraceptive devices (IUCDs). Fibrinolytic activity around IUCDs removed from 80 women was measured by embedding the device immediately after removal in a plasminogen-rich fibrin plate. In fifteen of the women an endometrial biopsy was also taken at the time of removal of the IUCD. In women who had the IUCDs removed because of bleeding a much higher fibrinolytic activity was found than in women not com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…This bleeding may be attributed to the trauma caused by the device increasing the plasminogen activator and free plasmin activity. This con- firms the report of Bonnar et al (4), who reported increased area of lysis in vitro caused by loops which were removed from women with menorrhagia.…”
Section: Women Wearing Lippes Loops and Cu-t(200)ssupporting
confidence: 85%
“…This bleeding may be attributed to the trauma caused by the device increasing the plasminogen activator and free plasmin activity. This con- firms the report of Bonnar et al (4), who reported increased area of lysis in vitro caused by loops which were removed from women with menorrhagia.…”
Section: Women Wearing Lippes Loops and Cu-t(200)ssupporting
confidence: 85%
“…Large numbers of macrophages or monocytes adhere to IUCDs, and higher cell counts were seen in menorrhagia and intermenstrual bleeding associated with significant fibrinolytic activity surrounding the device [17,18,33]. However, no increase was seen in association with the use of progesterone‐releasing device [19].…”
Section: Discussionmentioning
confidence: 99%
“…They are influenced by the cyclic variation of the sex hormone concentration at different phases of the menstrual cycle. Increased numbers of monocytes or macrophages known to adhere to intrauterine contraceptive devices (IUCDs) are associated with increased fibrinolytic activity in the endometrium [17,18], whereas no increase was seen on progesterone‐releasing devices [19]. In dysfunctional uterine bleeding (DUB), increased fibrinolytic activity was observed in the menstrual fluid and is suggested to be a major contributing factor in the etiology of menorrhagia [20].…”
Section: Introductionmentioning
confidence: 99%
“…These observations imply that the local differences in FA reported previously after application of plast and copper IUDs probably reflect a foreign body reaction [8,9]. However, the sutured tiny incision had no effect on the FA of the uterine segment with the scar, neither did such a mild surgical trauma influence the FA in the other segments of the uterine horn.…”
Section: Discussionmentioning
confidence: 91%